First record of Limnephilus affinis Curtis 1834 (Trichoptera: Limnephilidae) in the Azores - Zamora-Muñoz, Carmen (Zootaxa, 2014)
The Macaronesian Islands (the Azores, Madeira, the Canary and the Cape Verde Islands) are recognized as an important hotspot of Mediterranean biodiversity (Myers et al. 2000). Among the archipelagos, the Azorean terrestrial fauna is characterized by a lower percentage of endemism, and less species richness in general; about half of that known for the Canary Islands and 80% of that known for Madeira and the Selvagens (Borges et al. 2010). While in the Canary Islands and Madeira, 18 and 13 species have been respectively recorded (Hughes & Barnard 2008; Báez & Oromí 2010), the number of species of the trichopteran fauna of Azores Islands is very short. Up to now it has included only four species: Two Paleartic species, Hydroptila vectis Curtis 1834 and Oxyethira falcata Morton 1893; a Macaronesian endemic, Hydroptila fortunata Morton 1893; and an Azorean endemic, Limnephilus atlanticus Nybom 1948. Information on island occurrence of H. fortunata is not available, but the other three species are known to be well distributed in the archipelago (Borges 2010; Raposeiro et al. 2012).